2000
DOI: 10.1001/jama.284.8.984
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care for Patients With Rheumatoid Arthritis

Abstract: In this population, health care quality appears to be suboptimal for arthritis, comorbid disease, and health care maintenance. Patterns of care that included relevant specialists were associated with substantially higher quality across all domains. Patterns that included generalists were associated with substantially higher quality health care maintenance than patterns that included neither a generalist nor a relevant specialist. The optimal roles of primary care physicians and specialists in the care of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
166
2
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(177 citation statements)
references
References 52 publications
5
166
2
4
Order By: Relevance
“…These estimates likely understate the problem for the US as a whole, because recent studies demonstrate that the VA outperforms other systems in chronic disease management (9,23). These results confirm the findings by MacLean et al (8) of gaps in care quality for patients with rheumatic diseases, and extend their findings to include patients with gout. Results in this US VA population are similar to results from the UK.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These estimates likely understate the problem for the US as a whole, because recent studies demonstrate that the VA outperforms other systems in chronic disease management (9,23). These results confirm the findings by MacLean et al (8) of gaps in care quality for patients with rheumatic diseases, and extend their findings to include patients with gout. Results in this US VA population are similar to results from the UK.…”
Section: Discussionsupporting
confidence: 91%
“…Low adherence to quality indicators for treating various diseases has been found in many US health care systems (6,7), particularly for treatment of musculoskeletal diseases including rheumatoid arthritis (8), acute low back pain (6), and osteoarthritis (9), with quality scores ranging from 54% to 65%. MacLean et al (8) studied patients with rheumatoid arthritis enrolled in a nationwide US insurance company and reported quality scores of 62% for arthritis care, 52% for comorbid disease care, and 42% for health care maintenance. Higher scores were noted in patients who received relevant specialist or primary care compared with those who did not (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, even assignment of a specific diagnosis may still reflect uncertainty because it is preliminary and awaits later confirmation through testing or observation of disease evolution. One approach to improving ambulatory health care disease-based estimates has been to apply algorithms that search for multiple visits for the same condition over time in the same person (13). Unfortunately this is not possible in NAMCS/NHAMCS data given the short-term nature of the sampling at a site and the lack of individual identifiers.…”
Section: Sacks Et Almentioning
confidence: 99%
“…The failure to focus on comorbidity in the treatment of chronic diseases Several studies have shown that patients with 1 disease may be undertreated for other diseases (53,54), and RA is no exception (55,56). This may be partly the result of a confounding effect of age (57,58); that is, elderly patients are less likely to be treated, and elderly patients are also more likely to have a comorbid condition.…”
Section: Boers Et Almentioning
confidence: 99%